Long‐term anoxia and release of ancient, labile carbon upon thaw of Pleistocene permafrost. Issue 24 (23rd December 2015) - Ewing, Stephanie A.; O'Donnell, Jonathan A.; Aiken, George R.; Butler, Kenna; Butman, David; Windham‐Myers, Lisamarie; Kanevskiy, Mikhail Z.
Abstract: The fate of permafrost carbon upon thaw will drive feedbacks to climate warming. Here we consider the character and context of dissolved organic carbon (DOC) in yedoma permafrost cores from up to 20 m depth in central Alaska. We observed high DOC concentrations (4 to 129 mM) and consistent low molecular weight organic acid concentrations in three cores. We estimate a DOC production rate of 12 µmol DOC m −2 yr −1 based on model ages of up to 200 kyr derived from uranium isotopes. Acetate C accounted for 24 ± 1% of DOC in all samples. This proportion suggests long‐term anaerobiosis and is likely to influence thaw outcomes due to biolability of acetate upon release in many environments. The combination of uranium isotopes, ammonium concentrations, and calcium concentrations explained 86% of the variation in thaw water DOC concentrations, suggesting that DOC production may be related to both reducing conditions and mineral dissolution over time. Key Points: Aged, biolabile forms of DOC are present in Pleistocene permafrost Reducing conditions in yedoma produce biolabile DOC and characteristic solutes over time Both reducing conditions and mineral dissolution are related to permafrost DOC production